One-step synthesis of SBA-15 containing tungsten oxide nanoclusters: a chemoselective catalyst for oxidation of sulfides to sulfoxides under ambient conditions - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Chemical Communications, 2007)
Tungsten oxide nanoclusters supported highly ordered mesoporous SBA-15 material has been successfully synthesized in a single step using a non-ionic surfactant as a template and used for the selective oxidation of sulfur compounds, giving excellent yields at room temperature with exceptional catalyst recyclability.

Oxyfunctionalisation of adamantane using inorganic-organic hybrid materials based on isopoly and heteropoly anions: kinetics and mechanistic studies - Bordoloi, Ankur; Vinu, Ajayan; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2007)
{Oxyfunctionalisation of adamantane with 30% aq.H2O2 in butyronitrile solvent was efficiently catalyzed by inorganic-organic hybrid materials synthesized by the immobilisation of isopoly (WOx = sodium tungstate
Keywords: adamantane; inorganic-organic hybrid materials; oxyfunctionalisation; vanadium (V) superoxo intermediate

Heteropoly acid encapsulated SBA-15/TiO(2) nanocomposites and their unusual performance in acid-catalysed organic transformations - Sawant, Dhanashri P.; Justus, Josena; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Srinivasu, Pavuluri; Velmathi, Sivan; Halligudi, Shivappa B.; Vinu, Ajayan (Chemistry-A European Journal, 2008)
The preparation of SBA-15/TiO(2) nanocomposites with different loadings of Keggin-type 12-tungsto-phosphoric acid (TPA) nanocrystals in their mesochannels through a simple and effective vacuum impregnation method is reported for the first time. The catalysts have been characterised by various sophisticated techniques, including XRD, HRSEM, and TEM. It has been found that the acidity and the textural parameters of the nanocomposites can be controlled by simply changing the loadings of TPA and TiO(2) or the calcination temperature. TPA and TiO(2) loadings of 15 and 22.4 wt %, respectively, and a calcination temperature of 1123 K have proved to be optimal for obtaining mesoporous nanocomposite materials with the highest acidity. Moreover, the activities of these catalysts in promoting hydroamination as well as Mannich and Claisen rearrangement reactions have been extensively investigated. The results show that the amount of TPA has a great influence on the activity of the nanocomposites in all of the reactions studied. The effects of other reaction parameters, such as temperature and reaction time, on the conversion and product selectivity have also been studied in detail. A kinetic analysis of the formation of the products under various reaction conditions is presented. It has been found that the activity of the nanocomposite composed of 15 wt % TPA deposited on 22.4 wt of TiO(2) on SBA-15 in promoting the studied reaction is remarkably higher than the catalytic activities shown by pure TPA, TiO(2)-loaded SBA-15, or TPA-loaded SBA-15. The results obtained have indicated that the acidity and the structural control of the nanocomposite materials are highly critical for obtaining excellent catalytic activity, and the presented highly acidic nanocomposites are considered to show great potential for use as catalysts in promoting many acid-catalysed organic transformations.
Keywords: Bronsted acids; mesoporous materials; nanoreactors; nanotechnology; supported catalysts

Highly efficient and chemo selective catalyst system for the synthesis of blossom orange fragrance and flavoring compounds - Justus, Josena; Vinu, Ajayan; Devassy, Biju M.; Balasubramanian, Veerappan V.; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Catalysis Communications, 2008)
{Acetal and acylal formation reactions of organic compounds are efficiently catalyzed by zirconia-supported mixed oxide systems under liquid-phase reaction conditions. 15WZ-750 (where
Keywords: Acetal; acylal; Silicotungstic acid; tungsten oxide; tungstophosphoric acid; Zirconia

Non-phosgene route for the synthesis of methyl phenyl carbamate using ordered AISBA-15 catalyst - Lucas, Nishita; Amrute, Amol P.; Palraj, K.; Shanbhag, G. V.; Vinu, Ajayan; Halligudi, Shivaraj B. (Journal of Molecular Catalysis A-Chemical, 2008)
Methyl phenyl carbamate (MPC) has been synthesized Under liquid phase conditions from dimethyl carbonate and aniline by using mesoporous AISBA-15 catalyst. The catalyst with different Si/Al ratio was synthesized by isomorphous Substitution of aluminium into the framework of siliceous SBA-15. The structural integrity of the catalyst system was diagnosed with the help of various characterization techniques Such as X-ray diffraction, Surface analysis, and the acidity measurement has been done by TPD using ammonia as probe molecule. AISBA-15 (Si/Al = 10) exhibited highest catalytic activity in the synthesis of MPC under the reaction Conditions Studied. The effect of parameters Such as molar ratio of reactants, catalyst concentration. reaction temperature and time on the conversion of aniline was investigated. The results demonstrated that an aniline conversion of 99% and MPC selectivity of 71% were achieved when the reaction was carried out at 100 C, DMC to aniline mole ratio of 10 with 5% of catalyst (wt% of total reaction mixture) for 3 h. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: amines; Dimethyl carbonate; Mesoporous AISBA-15; Methoxycarbonylation; Methyl phenyl carbamate

Novel three dimensional cubic Fm3m mesoporous aluminosilicates with tailored cage type pore structure and high aluminum content - Srinivasu, Pavuluri; Alam, Sher; Balasubramanian, Veerappan V.; Velmathi, Sivan; Sawant, Dhanashri P.; Boehlmann, Winfred; Mirajkar, Subhash P.; Ariga, Katsuhiko; Halligudi, Shivappa B.; Vinu, Ajayan (Advanced Functional Materials, 2008)
Novel three dimensional cubic Fm3m mesoporous aluminosilicates (AIKIT-5) with very high structural order and unprecedented loadings of Al in the silica framework have been successfully prepared for the first time by using non ionic surfactant as a template in a highly acidic medium. The obtained materials have been unambiguously characterized in detail by several sophisticated techniques such as XRD, N, adsorption, HRTEM, HRSEM, EDS, elemental mapping, Al-27 MAS NMR, and NH3-TPD. We also demonstrate that the nature, and the amount of Al incorporation in the silica framework can easily be controlled by simply varying the n(H2O)/n(HCl) and the n(Si)/n(Al), ratios, and the Al sources in the synthesis gel. Among the Al sources examined, the Al isopropoxide (AiPr) is superior over other Al sources. Al-27 MAS NMR results reveal that the amount of tetrahedral Al in the framework can be controlled by simply adjusting the nSi/nAl ratio in the synthesis gel, which increases with increasing the Al incorporation. One of the interesting findings in the work is the increase of the specific surface area, specific pore volume and the pore diameter of AIKIT-5 with increasing the Al incorporation in the silica framework (up to n(Si)/n(Al), ratio of 10) while retaining the well-ordered three dimensional cage type porous structure, and the mechanism for the unusual behavior has been discussed in detail. Finally, the acidity and the catalytic activity in the acetylation of veratrole of the AIKIT-5 catalysts have been studied and the results have been compared with the several zeolites catalysts. Among the catalysts examined, AIKIT-5(10) is found to be superior over the zeolites catalysts such as mordenite, zeolite H-Y, zeolite H-beta, and ZSM-5.

Synthesis of biodiesel over zirconia-supported isopoly and heteropoly tungstate catalysts - Sunita, G.; Devassy, Biju M.; Vinu, Ajayan; Sawant, Dhanashri P.; Balasubramanian, Veerappan V.; Halligudi, Shivappa B. (Catalysis Communications, 2008)
The liquid-phase synthesis of biodiesel by transesterification of sunflower oil with methanol is carried out by using zirconia-supported isopoly and heteropoly tungstates (HPAs) as catalysts. The isopoly and heteropoly tungstate catalysts were prepared by suspending zirconium oxyhydroxide in water/methanol solution of ammonium metatungstate/silicotungstic acid, phosphotungstic acid (WO3/HPA loading, 15%,,) followed by drying and calcination at 750 degrees C. The catalysts were characterized by XRD, Raman spectroscopy, IR spectroscopy, NH3-TPD and FTIR pyridine adsorption spectroscopy. XRD results indicate that the presence of isopoly and heteropoly tungstates stabilizes ZrO2 in tetragonal phase. Raman and IR spectra of the catalysts show that tungstate species exist as zirconia-anchored octahedral mono-oxotungstate. The acidity measurements by NH3-TPD and FTIR pyridine adsorption spectroscopy show that zirconia-supported phosphotungstate has the highest total acidity and zirconia-supported isopoly tungstate has the highest Bronsted acidity. The zirconia-supported isopoly tungstate shows superior catalytic performance compared to zirconia-supported heteropoly tungstate catalysts. Under the reaction conditions of 200 degrees C and methanol/oil molar ratio 15, 15% WO3/ZrO2 calcined at 750 degrees C gave 97% conversion of oil. This catalyst also efficiently catalyzes methanolysis of other vegetable oils like mustard oil and sesame oil. The deactivated catalyst could be regenerated by calcination without appreciable loss in activity. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: Biodiesel; phosphotungstic acids; Silicotungstic acid; transesterification; tungsten oxide; Zirconia

Comparative study on liquid phase alkylation of 2-methylnaphthalene with long chain olefins using different solid acid catalysts - Lucas, Nishita; Bordoloi, Ankur; Amrute, Amol P.; Kasinathan, Palraj; Vinu, Ajayan; Bohringer, Walter; Fletcher, Jack C. Q.; Halligudi, Shivaraj B. (Applied Catalysis A-General, 2009)
A comparative study has been made over a variety of solid acid catalysts, which include isopoly and heteropoly ions supported on various supports such as zirconia, titania, a large variety of zeolites and a couple of mesoporous materials for liquid phasealkylation of 2-methylnaphthalene with 1-octene.All the catalyst systems were characterized by nitrogen sorption analysis, X-ray diffraction and NH(3)-TPD. Inspite of their high acid amounts zeolites gave poor catalytic performance due to their diffusional constraints; on the other hand mesoporous materials lacked diffusional constraints but due to their low acid amounts resulted in poor conversions. lsopoly and heteropoly ions supported on zirconia and titania were found to be catalytically active for the reaction due to total surface acidity. Among them, isopolytungstate supported on zirconia exhibited the best catalytic activity and was used for further optimization of reaction conditions. Excellent conversions of all olefins (>92%) with high selectivity of monoalkylmethylnaphthalene (>95%) was obtained under optimized reaction conditions. The catalyst could be recycled for several times without any obvious loss of its activity. (C) 2008 Elsevier B.V. All rights reserved.
Keywords: 2-Methylnaphthalene; Alkylation; Long chain olefins; Zirconia

Titania nanoparticles stabilized HPA in SBA-15 for the intermolecular hydroamination of activated olefins - Sawant-Dhuri, Dhanashri; Balasubramanian, Veerappan V.; Ariga, Katsuhiko; Park, Dae-Hwan; Choy, Jin-Ho; Cha, Wang Soo; Al-deyab, Salem S.; Halligudi, Shivappa B.; Vinu, Ajayan (ChemCatChem, 2014)
A liquid phase hydroamination (HA) of alpha,beta-ethylenic compounds with amines was investigated with TiO2 nanoparticles stabilized 12-tungstophosphoric acid (TPA) in SBA-15. The catalysts were prepared by wet impregnation of TPA/TiO2 nanoparticles into the SBA-15 and calcined at different temperatures. The characterization results reveal that the textural properties and the acidity of the prepared catalysts can be finely controlled with the simple adjustment of the calcination temperature and the structure of the support, decorated with the TiO2 and TPA nanoparticles, was intact even after the modification. The prepared catalysts were investigated for HA of ethyl acrylate with different aromatic and aliphatic amines over a wide range of reaction conditions to optimize the yield and the selectivity of product. It was found that this process is 100% atom efficient and the catalytic performance depended significantly on the loading of TPA over the catalyst and the calcination temperature. Under optimized reaction conditions, the best catalyst, 15 wt% TPA/22.4 wt% TiO2/SBA-15 calcined at 1123 K, offered the highest conversion of p-ethylaniline (70%) with 100% chemo-selectivity to the anti-Markovnikov product, i.e., the mono-addition product. The reaction was heterogeneously catalyzed and no contribution from leached TPA into the reaction was observed.
Keywords: heteropoly acids; hydroamination; mesoporous materials; nanocatalysts

Freestanding borophene and Its hybrids - Ranjan, Pranay; Sahu, Tumesh Kumar; Bhushan, Rebti; Yamijala, Sharma S. R. K. C.; Late, Dattatray J; Kumar, Prashant; Vinu, Ajayan (Advanced Materials, 2019)
Borophene, an elemental metallic Dirac material is predicted to have unprecedented mechanical and electronic character. Need of substrate and ultrahigh vacuum conditions for deposition of borophene restricts its large-scale applications and significantly hampers the advancement of research on borophene. Herein, a facile and large-scale synthesis of freestanding atomic sheets of borophene through a novel liquid-phase exfoliation and the reduction of borophene oxide is demonstrated. Electron microscopy confirms the presence of beta(12), X-3, and their intermediate phases of borophene; X-ray photoelectron spectroscopy, and scanning tunneling microscopy, corroborated with density functional theory band structure calculations, validate the phase purity and the metallic nature. Borophene with excellent anchoring capabilities is used for sensing of light, gas, molecules, and strain. Hybrids of borophene as well as that of reduced borophene oxide with other 2D materials are synthesized, and the predicted superior performance in energy storage is explored. The specific capacity of borophene oxide is observed to be approximate to 4941 mAh g(-1), which significantly exceeds that of existing 2D materials and their hybrids. These freestanding borophene materials and their hybrids will create a huge breakthrough in the field of 2D materials and could help to develop future generations of devices and emerging applications.

Direct synthesis of mesoporous siliceous phosphotungstic acid and its superior catalytic activity on the cyclohexylation of phenol - Ilbeygi, Hamid; Sawant, Dhanashri P.; Ruban, Sujanya M.; Reshma, Kokane S.; Umbarkar, Shubhangi B.; Halligudi, Shivappa B.; Vinu, Ajayan (Journal of Physical Chemistry C, 2021)
The synthesis of highly active and reusable mesoporous siliceous phosphotungstic acid materials (mPTA-Si) which are prepared through a simple self-assembly between phosphotungstic acid (PTA), the polymeric surfactant, and the silica precursor assisted by KCl for cyclohexylation of phenol is reported. The surface area and the acidity of these materials are tuned with a simple adjustment of PTA in the silica framework. The prepared samples exhibit mesoporous structure with a high surface area, but the structure is collapsed when the loading of PTA is high. It is established that the Keggin structure of PTA is retained on the final mPTA-Si. mPTA-Si with different loadings of PTA are employed as the catalysts for the cyclohexylation of phenol under liquid phase conditions. Among the catalysts studied, 10.0-mPTA-8.3Si calcined at 350 degrees C is found to be highly active, selective, and recyclable and offers 100% conversion of phenol with the highest selectivity for p-cyclohexylphenol (96.8%).